GlotEval: A Test Suite for Massively Multilingual Evaluation of Large Language Models - Luo, Hengyu; Li, Zihao; Attieh, Joseph; Devkota, Sawal; de Gibert, Ona; Huang, Xu; Ji, Shaoxiong; Lin, Peiqin; Mantina; Bhavani Sai Praneeth Varma; Sreenidhi, Ananda; Vázquez, Raúl; et al. (United States, 2026)
Large language models (LLMs) are advancing at an unprecedented pace globally, with regions increasingly adopting these models for applications in their primary languages. Evaluating these models in diverse linguistic environments, especially in low-resource languages, has become a major challenge for academia and industry. Existing evaluation frameworks suffer from inconsistency across different benchmarks, being disproportionately focused on English and a handful of high-resource languages, thereby overlooking the realistic performance of LLMs in multilingual and lower-resource scenarios. To address this critical challenge of fragmented and inconsistent multilingual evaluation, we introduce GlotEval, a unified and lightweight framework that systematically integrates 27 benchmarks under a standardized ISO 639-3 language identifier system, allowing for seamless incorporation of new benchmarks. Supporting nine key tasks (machine translation, text classification, summarization, open-ended generation, reading comprehension, sequence labeling, intrinsic evaluation, instruction following and reasoning), spanning over dozens to hundreds of languages, GlotEval uniquely enables language-specific, cross-benchmark analysis and non-English-centric evaluations at a scale previously less practical for many researchers. This enables a precise diagnosis of model strengths and weaknesses in diverse linguistic contexts. A multilingual translation case study demonstrates GlotEval’s applicability for multilingual and language-specific evaluations.
Proceedings of the 2025 Conference on Empirical Methods in Natural Language Processing : System Demonstrations